Energy Efficiency and the Transition to Renewables—Building Communities of the Future - Efstathios E. Michaelides (Energies)
The effects of energy efficiency on the decarbonization engineering infrastructure were examined by simulating the hourly energy demand of a small Texan city with 10,000 buildings. The available renewable energy sources in the region, wind and solar, supply the required energy, and the deficit or surplus is offset by energy storage. The demand–supply match during every hour of the year determines the required renewable power, the energy storage requirement, and dissipation in the energy storage/regeneration processes. The computations showed that the implementation of energy efficiency measures will decrease the total required renewable power by a factor of 2.9, the needed energy storage by a factor of 2.0, and the annual energy dissipation by a factor of 2.4. Of particular interest is the determination of the energy transition elasticity coefficients, which offer quantitative interpretation and a better understanding of the effects of energy efficiency measures on the decarbonization efforts of communities.